Comparative Study of Semiconductors Bismuth Iodate, Bismuth Triiodide and Bismuth Trisulphide Crystals - T.K. Patil; M.I. Talele (Журнал нано- та електронної фізики)
In the present investigation, crystals of Bismuth Iodate[Bi(IO3)3], Bismuth Iodide[BiI3] and Bismuth- Tri Sulphide [Bi2S3] were grown by a simple gel technique using single diffusion method. The optimum growth conditions were established by varying various parameters such as pH of gel solution, gel concentration, gel setting time, concentration of reactant etc. Gel was prepared by mixing sodium meta silicate (Na2SiO35H2O), glacial acetic acid (CH3COOH) and supernant bismuth chloride (BiCl3) at pH value 4.4 and transferred in glass tube of diameter 2.5 cm and 25 cm in length. The mouth of test tube was covered by cotton plug and kept it for the setting. After setting the gel, it was left for aging. After 13 days duration the second supernant K(IO3), KI3 and H2S water gas solution was poured over the set gel by using pipette then it was kept undisturbed. After 72 hours of pouring the second supernatant, the small nucleation growth was observed at below the interface of gel. The good quality crystals of [Bi(IO3)3], [BiI3] and [Bi2S3] were grown. These grown crystals were characterized by XRD, FTIR, Chemical Analysis and Electrical Conductivity.